2018
DOI: 10.1186/s40862-018-0045-3
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the components of the foreign language classroom anxiety scale in the context of Japanese undergraduates

Abstract: This study aimed to investigate the latent constructs in the Foreign Language Classroom Anxiety Scale using a research context of Japanese undergraduates who learn English as a foreign language. The study conducted both exploratory and confirmatory factor analysis against two different groups of Japanese undergraduate students. First, exploratory factor analysis was used to extract factors from 33 items of the scale in its application to 149 management major students. Subsequently, confirmatory factor analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 22 publications
(94 reference statements)
1
29
0
1
Order By: Relevance
“…Appendix B in Data S1 indicates that CA as a construct represented 61% of the FLCAS. CA involves social and interpersonal aspects, as well as individual attributes (Toyama & Yamazaki, 2018). The emotional aspect of CA was examined in 12 items, and its somatic manifestations were explored in 5 items.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Appendix B in Data S1 indicates that CA as a construct represented 61% of the FLCAS. CA involves social and interpersonal aspects, as well as individual attributes (Toyama & Yamazaki, 2018). The emotional aspect of CA was examined in 12 items, and its somatic manifestations were explored in 5 items.…”
Section: Resultsmentioning
confidence: 99%
“…Horwitz et al (1986) argued the FLCAS construct validity is maintained by the small amount of shared variance between it and other FLA measures. CA and TA accounted for 58.56% of the total variance of the FLCAS (Toyama & Yamazaki, 2018). All items produced significant corrected item‐total correlations, and the test–retest reliability over 8 weeks yielded r = 0.83 ( p < 0.001) (Horwitz, 1986; Horwitz & Young, 1991).…”
Section: Methodsologymentioning
confidence: 99%
See 1 more Smart Citation
“…The washback effect often means that students' experience of English from 12 to 18 years old involves little exposure to communicative approaches and few opportunities to speak English aside from pronunciation (Gorsuch, 1998;Hino, 1988;Nishino & Watanabe, 2008;Osterman, 2014). Toyama and Yamazaki's (2018) findings confirm the influence of this learning experience of Japanese university students. Using a factor analysis for the components of the Foreign Language Classroom Anxiety Scale (FLCAS) (Horwitz et al, 1986) they found that communication apprehension and test anxiety were prevalent.…”
Section: Negative Emotions In Foreign Language Classroom and Foreign mentioning
confidence: 74%
“…For each item analysis, to judge whether an item was maintained or eliminated, we required (a) a factor loading of at least 0.50 as the cutoff point for a 163 sample size, which lies between 100 and 200 (Field, 2013); (b) at least three items per factor (Costello & Osborne, 2005); and (c) elimination of a complex item with cross-loading that is difficult to interpret (Yong & Pearce, 2013). This method of evaluation was previously adopted to investigate latent variables of the Foreign Language Anxiety Classroom Scale (Toyama & Yamazaki, 2018).…”
Section: Ip Measure Validationmentioning
confidence: 99%